Co-stimulatory signaling determines tumor antigen sensitivity and persistence of CAR T cells targeting PSCA+ metastatic prostate cancer. (1st February 2018) - Priceman, Saul J.; Gerdts, Ethan A.; Tilakawardane, Dileshni; Kennewick, Kelly T.; Murad, John P.; Park, Anthony K.; Jeang, Brook; Yamaguchi, Yukiko; Yang, Xin; Urak, Ryan; Weng, Lihong; Chang, Wen-Chung; et al.
ABSTRACT: Advancing chimeric antigen receptor (CAR)-engineered adoptive T cells for the treatment of solid cancers is a major focus in the field of immunotherapy, given impressive recent clinical responses in hematological malignancies. Prostate cancer may be amenable to T cell-based immunotherapy since several tumor antigens, including prostate stem-cell antigen (PSCA), are widely over-expressed in metastatic disease. While antigen selectivity of CARs for solid cancers is crucial, it is problematic due to the absence of truly restricted tumor antigen expression and potential safety concerns with "on-target off-tumor" activity. Here, we show that the intracellular co-stimulatory signaling domain can determine a CAR's sensitivity for tumor antigen expression. A 4-1BB intracellular co-stimulatory signaling domain in PSCA-CARs confers improved selectivity for higher tumor antigen density, reduced T cell exhaustion phenotype, and equivalent tumor killing ability compared to PSCA-CARs containing the CD28 co-stimulatory signaling domain. PSCA-CARs exhibit robust in vivo anti-tumor activity in patient-derived bone-metastatic prostate cancer xenograft models, and 4-1BB-containing CARs show superior T cell persistence and control of disease compared with CD28-containing CARs. Our study demonstrates the importance of co-stimulation in defining an optimal CAR T cell, and also highlights the significance of clinically relevant models in developing solid cancer CAR T cell therapies.